Style Leadership Head School Muhammadiyah 1 Senior High School Karanganyar in Institutional Quality Management Education - Suwandi, Suwandi; Narimo, Sabar; Zakki Azani, Mohammad (Universitas Muhammadiyah Surakarta, 2024)
Principal leadership plays a strategic role in managing the quality of educational institutions, including managerial aspects, entrepreneurial development, and supervision. This study aims to describe the leadership style of the principal of SMA Muhammadiyah 1 Karanganyar and its impact on the management of educational quality. The study used a qualitative method with a field approach. research. Data were obtained through observation, interviews, and documentation with the research subjects of the principal, teachers, staff, guardians, and students. The results of the study showed that the principal applied a combination of democratic, transformative, and transactional leadership style. The democratic style is demonstrated through the involvement of all elements of the school in policy making, creating a collaborative working atmosphere. The transformative style is reflected in the provision of inspiration and innovation through superior programs such as ICT classes, ICP, boarding class, and S2 scholarships for teachers. Meanwhile, the transactional style is seen in the awarding of awards to outstanding teachers and students. The combination of these styles contributes to improving the quality of education, marked by increased teacher competence, an Islamic school environment, and student achievement in both academic and non-academic fields. This study concludes that the principal's leadership style plays an important role in supporting the achievement of the school's vision and mission, namely producing outstanding, skilled, and noble cadres. These findings provide practical recommendations for principals in reflecting on the management of educational quality.